2022
DOI: 10.7759/cureus.26491
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hematomas Using a Synthetic Hybrid-Scale Fiber Matrix

Abstract: Effective treatment of traumatic subcutaneous hematomas is important to avoid complications, including skin necrosis, infection, scarring, hyperpigmentation, tissue edema, and prolonged recovery. Hematoma treatment may include evacuation followed by application of a skin substitute. Given the challenges associated with conventional skin substitutes, a fully-synthetic, resorbable, electrospun matrix composed of hybrid-scale fibers may offer a new option for treating hematomas. The present study reports on two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A limited number of electrospun scaffold products have been successfully translated into human clinical use due to the challenges associated with commercialization, including the time and cost associated with product development under FDA design controls, implementation of commercial scale manufacturing, regulatory clearance activities and product distribution. Despite these challenges, recent work by our group has demonstrated the successful design and clinical translation of a novel electrospun hybrid-scale fiber matrix for use in wound management [17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Since receiving FDA clearance in 2017, this electrospun matrix has been utilized in multiple clinical and surgical settings and a variety of different wound types and clinical indications [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limited number of electrospun scaffold products have been successfully translated into human clinical use due to the challenges associated with commercialization, including the time and cost associated with product development under FDA design controls, implementation of commercial scale manufacturing, regulatory clearance activities and product distribution. Despite these challenges, recent work by our group has demonstrated the successful design and clinical translation of a novel electrospun hybrid-scale fiber matrix for use in wound management [17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Since receiving FDA clearance in 2017, this electrospun matrix has been utilized in multiple clinical and surgical settings and a variety of different wound types and clinical indications [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, recent work by our group has demonstrated the successful design and clinical translation of a novel electrospun hybrid-scale fiber matrix for use in wound management [17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Since receiving FDA clearance in 2017, this electrospun matrix has been utilized in multiple clinical and surgical settings and a variety of different wound types and clinical indications [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The present review demonstrates the use of a synthetic hybrid-scale fiber matrix in clinical practice and offers collective insight into the efficacy and value of a hybrid-scale fiber matrix across multiple use cases in the wound care and soft tissue repair setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a 2018 study showed that 85% of 82 chronic wounds of varying wound origins, such as non-healing (diabetic, venous leg, pressure) ulcers and traumatic, vascular, necrotic, and surgical wounds, healed within 12 weeks after initial treatment with the SEFM (13). Additionally, numerous studies have demonstrated successful SEFM treatment of closing complex surgical wounds to assist in secondary healing or stimulate the formation of granulation tissue necessary for staging reconstructive procedures, such as flaps or skin grafting (13)(14)(15)(16)(17)(18). However, there have been no documented clinical uses of an SEFM in irradiated tissue for enhanced wound healing.…”
Section: Introductionmentioning
confidence: 99%